2014
DOI: 10.1128/jb.01354-13
|View full text |Cite
|
Sign up to set email alerts
|

Global Metabolic Response of Enterococcus faecalis to Oxygen

Abstract: cOxygen and oxidative stress have become relevant components in clarifying the mechanism that weakens bacterial cells in parallel to the mode of action of bactericidal antibiotics. Given the importance of oxidative stress in the overall defense mechanism of bacteria and their apparent role in the antimicrobial mode of action, it is important to understand how bacteria respond to this stress at a metabolic level. The aim of this study was to determine the impact of oxygen on the metabolism of the facultative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Thus, the present study evaluated the in vitro antibacterial activity of BR and CS against E. faecalis . Enterococcus faecalis is a Gram-positive facultative anaerobe and is able to grow in the presence or absence of oxygen [ 60 , 61 ]. E. faecalis was selected in our research because it is a microorganism and predominant bacteria found in persistent endodontic infections and in failed root canal treatment cases [ 58 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study evaluated the in vitro antibacterial activity of BR and CS against E. faecalis . Enterococcus faecalis is a Gram-positive facultative anaerobe and is able to grow in the presence or absence of oxygen [ 60 , 61 ]. E. faecalis was selected in our research because it is a microorganism and predominant bacteria found in persistent endodontic infections and in failed root canal treatment cases [ 58 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the bacterium could have adopted an alternative metabolic mode under oxygen limitation, leading to higher production of algicidal metabolites which far outweighed the drawback of reduced cell yield, which ultimately resulted in dramatically enhanced algicidal activity. Many studies have reported the significant effect of oxygen availability, on the biochemical properties of bacteria (McCloskey et al 2014 ; Partridge et al 2007 ; Portela et al 2014 ; Shan et al 2012 ; Trotter et al 2011 ). Aerobic respiration is conventionally the favored metabolic mode as compared to microaerobic respiration.…”
Section: Discussionmentioning
confidence: 99%
“…1d ). This included pathways for indole and glutamate metabolism ( 19 , 20 ). Indeed, these pathways have previously been linked with tolerance to antibiotics ( 9 , 21 , 22 ).…”
Section: Observationmentioning
confidence: 99%